How do you solve #4( 6x - 1) = 7( 3x + 2)#?

1 Answer

Answer:

Distribute and then combine.

Explanation:

You would have to distribute the #4# into #6x-1#, making it

#24x-4#

Doing the same on the other side, you have

#21x+14#

Your equation should now be

#24x-4 = 21x+14#

You have to combine like terms by subtracting and adding from each side. If you subtract #21x# from each side and add #4# to each side, you will end up with the equation

#3x=18#

Divide both sides by #3# and you get

#x=6#